Relationship between Self efficacy and Academic Performance among Orphaned Secondary School Students in Kenya - Oyuga, Patricia A.; Raburu, Pamela A.; Aloka, Peter J. O. (My University, 2019)
The study investigated the relationship between academic self-efficacy and academic performance among orphaned secondary school students in Kenya. The research was anchored on Social Cognitive theory. The study adopted concurrent triangulation research design within the mixed method approach. The target population comprised 300 orphaned students and 35 principals. A total of 300 orphaned students in secondary schools and 11 principals were selected through saturated and simple random sampling strategies respectively to form the representative sample. Students’ questionnaires, document analysis and interview guide for the head teachers were the main data collection instruments. In ensuring reliability, a pilot study was carried out using 75 students from and 5 head teachers from Rarieda Sub-Country who were not part of the representative sample in the study. Validity of research instrument was ensured by the university lecturers’ and supervisors’ expert judgment. A reliability coefficient of 0.891was reported. Quantitative data was analyzed using descriptive statistics (frequency and percentages) and inferential statistics (Pearson correlation and regression analysis) while qualitative data was analyzed using thematic analysis. SPSS version 24 was used to conduct the analyses. Study findings revealed a significant weak (small) positive relationships between self-efficacy belief and academic performance (r=.276). Results from the interviews revealed that’ self-efficacy is a vital component to academic performances amongst orphan students in Bondo Sub-County. Ministry of Education and other stakeholders should understand the plight of orphans and provide them with improved services like trained counsellors who would be able to provide orphaned students with appropriate counselling services in relation to self-regulation skills.
Keywords: Academic self-efficacy; Academic performance; Orphans; Secondary school; Students Kenya